Seminar Parenting: Membentuk Karakter 4.0 Anak Melalu Peran Bimbingan Orang Tua - Sabariah, Sabariah; Muhyatun, Muhyatun (STAI Publisistik Thawalib Jakarta, 2023)
The purpose of the seminar is to provide participants with knowledge about the role of parental guidance in shaping the character of 4.0 in children. The implementation method is face-to-face with a duration of 3.5 hours. The equipment used is an LCD projector, laptop, manual, sound system, table, and chairs. Service flow: forming a committee; designing guidebooks, banners, and flyers; making invitations; implementation of seminars and evaluation of seminars. The results of the dedication: the seminar was successful with the following agenda: first the opening by the head of the study program; second, giving material I about character education, character 4.0 in children and the role of parents; third, the provision of material on approaches and guidance techniques; fourth discussion and fifth group photo. Conclusion: the seminar went according to the agenda. Suggestion: the seminar committee provides mini-assignments for seminar participants.